NANOCOMPOSITE FLAT SHEET MEMBRANE FROM NANOCELLULOSE AND NANOZEOLITE ACTIVE AGENT WITH THE ADDITION OF MICROCELLULOSE FOR DESALINATION APPLICATION - Wahyu Edison, Rizky
Salt water desalination is one of solution to provide clean water supplies other than ground water and surface water to meet the needs of clean water for human, the supply will decrease due to the increasing of the human population. Zeolites particle are known to have better mechanical properties, thermal and chemical stability than organic materials, and have molecular sieve and ion exchange properties that have the potential to be used as desalination membranes. In previous studies flat sheet membranes were made using nanocellulose as a matrix or support and nanozeolite as active agents and chitosan as a binder. The membrane has good strength and high flexibility. Disadvantage of the membrane is it has not been able to separate the salt molecules from the water and the process pressure is still above 10 bar. To overcome the disadvantage, in this study a flat sheet membrane was developed by varying the concentration of chitosan and the addition of microcellulose. In this study, synthesis of NaA nanozeolite particles with Linde Type A structure is done with composition 4Na2O : 0,3Al2O3 : SiO2 : 200H2O in the form of white powder. Source of nanocellulose used comes from nata de banana skin. Membrane production is carried out in two stages, the first stage is making membranes with varying the concentration of chitosan by 0.25%, 0.5%, 1%, and 2% and looking for the most optimum concentration of chitosan. The second stage is making membranes with optimum chitosan concentration obtained from the first stage and microcellulose is added as much as 5%, 10%, 15%, 20%, and 25% of the total weight. The membranes was done by pulverizing the nanocellulose and microcellulose mixture and mixing with nanozeolite particles which have been mixed with 15 mL chitosan solution. Molding was done on petri dish with diameter of 6 cm and dried using a fan at room temperature. From the results of the desalination test the optimum concentration of chitosan obtained is 1% while the membrane with the addition of microcellulose as much as 20% of the total weight is the membrane with the highest flux value and salt rejection value.